The Flowers of...Epiphany - Jiana Shah (Surat, India White Falcon Publishing, 2021)
Whimsical, dreamy, and relatable, these poetries explore day-to-day life from various lenses, thusdwelling deeper into the misty pensive of thought.
Keywords: Poetry -- Poetry